2013
DOI: 10.1088/1478-3975/10/5/056003
|View full text |Cite
|
Sign up to set email alerts
|

Platelet size and density affect shear-induced thrombus formation in tortuous arterioles

Abstract: Thrombosis accounts for 80% of deaths in patients with diabetes mellitus. Diabetic patients demonstrate tortuous microvessels and larger than normal platelets. Large platelets are associated with increased platelet activation and thrombosis, but the physical effects of large platelets in the microscale processes of thrombus formation are not clear. Therefore, the objective of this study was to determine the physical effects of mean platelet volume (MPV), mean platelet density (MPD), and vessel tortuosity on pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 82 publications
3
29
0
Order By: Relevance
“…53 Analysis of the effect of MPV on thrombus formation using computational modeling showed that a higher MPV is favorable to thrombus formation 54 ; accordingly, we do not expect that the lower MPV observed in Pf4-Lox tg/tg platelets accounts for the propensity of thrombus formation in this model. The decrease in MPV cannot be attributed to changes in megakaryocyte ploidy levels because LOX did not affect ploidy in the current model.…”
Section: Org Frommentioning
confidence: 86%
“…53 Analysis of the effect of MPV on thrombus formation using computational modeling showed that a higher MPV is favorable to thrombus formation 54 ; accordingly, we do not expect that the lower MPV observed in Pf4-Lox tg/tg platelets accounts for the propensity of thrombus formation in this model. The decrease in MPV cannot be attributed to changes in megakaryocyte ploidy levels because LOX did not affect ploidy in the current model.…”
Section: Org Frommentioning
confidence: 86%
“…4 Moreover, diabetic patients display tortuous micro-vessels and large platelets; the extent of tortuosity is an important factor in shear-induced thrombosis in micro-vessels. 5 Thrombosis accounts for 80% of deaths in patients with diabetes mellitus who have an increased risk of developing sepsis and infection, particularly in intensive care units. 5,6 Diabetes mellitus and septic shock increase the production of reactive oxygen species (ROS) and pro-inflammatory cytokines, involving particularly the kallikrein-kinin system.…”
mentioning
confidence: 99%
“…5 Thrombosis accounts for 80% of deaths in patients with diabetes mellitus who have an increased risk of developing sepsis and infection, particularly in intensive care units. 5,6 Diabetes mellitus and septic shock increase the production of reactive oxygen species (ROS) and pro-inflammatory cytokines, involving particularly the kallikrein-kinin system. 7 Kinin B1 receptor (B1R), an important component of this system, is upregulated by endotoxins and may represent a therapeutic target in sepsis, yet its contribution in the acute phase of lipopolysaccharide (LPS)-induced endotoxin shock remains controversial.…”
mentioning
confidence: 99%
“…Our previous work (Chesnutt and Han, 2013) showed that our activation model was either in quantitative or qualitative agreement with a shear-induced platelet activation model that accounted for magnitude of and exposure time to shear stress (Alemu and Bluestein, 2007), depending on the parameters chosen for the model of Alemu and Bluestein.…”
Section: Discussionmentioning
confidence: 52%